Constitutive model of high-temperature rapid fracture of Si3N4 ceramics for engine turbine discs and their pore insensitivity parameters - JS Peng; FY Li; SJ Ma; XH Dong; XP Zhang (Journal of Asian Ceramic Societies)
The metallic materials used to manufacture turbine components can potentially be replaced with ceramics such as Si3N4, but the stress on turbine discs is difficult to determine experimentally, which hinders the development and optimization of ceramics. The finite element method solves this problem, but it requires an accurate constitutive model and parameters. Existing methods for determining model parameters lack versatility and do not consider the internal pores of ceramics. This work proposes a method for determining the parameters of the high-temperature rapid fracture constitutive model of ceramics with internal pores based on the results of industrial computed tomography (CT) and high-temperature fracture toughness experiments. The constitutive model for a ceramic with internal pores was selected based on the typical service conditions of turbine discs. Industrial CT was used to measure pore information. A finite element preprocessor was developed to create simulated specimens with pores. The high-temperature fracture toughness of the ceramics was measured. Pore insensitivity was the parameter obtained from the high-temperature constitutive model of ceramics with pores using this method. The maximum relative error between the predicted and experimental flexural strengths was 6.8%. It provides a new idea for determining the parameters of constitutive models for materials with pores.